Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

how to solve this equation:

$(Px-y)(Py+x)=h^2P$

that $P=\frac{dy}{dx}$

and $h$ is a constant.

share|cite|improve this question
    
Typically, one tries to find an integrating factor... Your equation looks a bit suspicious. Is it homework/exercise in a book? Did you copy the problem correctly? As it is stated it is not a second order DE, but a (quite nonlinear) first order DE. – Fabian May 3 '11 at 7:12
    
this is a homework,i say "I know it gets First Order" because our lesson treat on FO DE :D,its equal to : $xyP^2+(x^2-y^2-h^2)P-xy=0$, can help? – Doman May 3 '11 at 7:23
    
It's a first order ODE, since it involves $y(x)$ and the first derivative $y'(x)$. (Not higher derivatives like $y''(x)$ etc.) What's your question, exactly? – Hans Lundmark May 3 '11 at 7:42
    
@Doman: even when there is $P^2$ it is still a first order ODE (no $y''(x)$ appearing). It is just a nonlinear differential equation. – Fabian May 3 '11 at 7:55
    
@All:thanks, what a bad mistake :D. Q EDITED. – Doman May 3 '11 at 14:01

Assume $h\neq0$ for the key case:

Let $u=x^2+y^2$ ,

Then $\dfrac{du}{dx}=2x+2y\dfrac{dy}{dx}$

$\therefore\left(\dfrac{x}{2y}\left(\dfrac{du}{dx}-2x\right)-y\right)\dfrac{1}{2}\dfrac{du}{dx}=\dfrac{h^2}{2y}\left(\dfrac{du}{dx}-2x\right)$

$\left(x\left(\dfrac{du}{dx}-2x\right)-2y^2\right)\dfrac{du}{dx}=2h^2\left(\dfrac{du}{dx}-2x\right)$

$x\dfrac{du}{dx}-2x^2-2y^2=2h^2\left(1-\dfrac{2x}{\dfrac{du}{dx}}\right)$

$x\dfrac{du}{dx}-2u=2h^2-\dfrac{4h^2x}{\dfrac{du}{dx}}$

$2u+2h^2=x\dfrac{du}{dx}+\dfrac{4h^2x}{\dfrac{du}{dx}}$

$u+h^2=\dfrac{x}{2}\dfrac{du}{dx}+\dfrac{2h^2x}{\dfrac{du}{dx}}$

Let $v=x^2$ ,

Then $\dfrac{du}{dx}=\dfrac{du}{dv}\dfrac{dv}{dx}=2x\dfrac{du}{dv}$

$\therefore u+h^2=x^2\dfrac{du}{dv}+\dfrac{h^2}{\dfrac{du}{dv}}$

$u+h^2=v\dfrac{du}{dv}+\dfrac{h^2}{\dfrac{du}{dv}}$

Let $s=u+h^2$ ,

Then $\dfrac{ds}{dv}=\dfrac{du}{dv}$

$\therefore s=v\dfrac{ds}{dv}+\dfrac{h^2}{\dfrac{ds}{dv}}$

$s\dfrac{dv}{ds}=v+\dfrac{h^2}{\left(\dfrac{ds}{dv}\right)^2}$

$v=s\dfrac{dv}{ds}-h^2\left(\dfrac{dv}{ds}\right)^2$

Which reduces to Clairaut's ODE.

$\dfrac{dv}{ds}=s\dfrac{d^2v}{ds^2}+\dfrac{dv}{ds}-2h^2\dfrac{dv}{ds}\dfrac{d^2v}{ds^2}$

$\dfrac{d^2v}{ds^2}\left(2h^2\dfrac{dv}{ds}-s\right)=0$

$\therefore\begin{cases}\dfrac{d^2v}{ds^2}=0\\2h^2\dfrac{dv}{ds}-s=0\end{cases}$

$\begin{cases}v=as+b\\v=\dfrac{s^2}{4h^2}+c\end{cases}$

$\therefore\begin{cases}as+b=as-h^2a^2\\\dfrac{s^2}{4h^2}+c=\dfrac{s^2}{2h^2}-\dfrac{s^2}{4h^2}\end{cases}$

$\begin{cases}b=-h^2a^2\\c=0\end{cases}$

$\therefore\begin{cases}v=as-h^2a^2\\v=\dfrac{s^2}{4h^2}\end{cases}$

$\begin{cases}x^2=au+h^2a-h^2a^2\\x^2=\dfrac{(u+h^2)^2}{4h^2}\end{cases}$

$\begin{cases}x^2=ax^2+ay^2+h^2a-h^2a^2\\x^2=\dfrac{(x^2+y^2+h^2)^2}{4h^2}\end{cases}$

$\begin{cases}(a-1)x^2+ay^2=h^2a^2-h^2a\\x^2=\dfrac{(x^2+y^2+h^2)^2}{4h^2}\end{cases}$

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.